Islam Dan Studi Agama-Agama: Telaah Atas Buku Approaches To Islam In Religious Studies Karya Ricard C. Martins - Rubi Babullah; Yurna Yurna; Siti Ulfah Fauziah; Ujang Nata Direja; Neneng Nur (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Islam gained great attention in the study of religion due to the development and global influence on the world Muslim population. An understanding of Islam as a religion and understanding of religion from the viewpoint of Islam is an issue that needs to be elaborated in the discussion and the discussion in the field of religious studies. The failure of religious studies to standardize itself as a 'discipline', although many emerging religious studies. The position of those who want to ask